Pengaruh Fair Value Accounting Dan Dewan Komisaris Terhadap Earning Management Yang Dimoderasi Oleh Peran Syariah - Restu Hanin Annisa; Salma Taqwa (Jurnal Eksplorasi Akuntansi, 2020)
The purpose of this study is to determine the effect of fair value accounting and board of commissioners on earnings management. The renewal of this study where the research also aims to determine the role of sharia in moderating the influence of fair value accounting and the board of commissioners on earnings management. Researchers tested banking companies listed on the Indonesia Stock Exchange in 2015-2018 with a total sample of 152 samples using a purposive sampling method. The results showed that fair value accounting and the board of commissioners had no effect on earnings management, where the probability value of both was greater than the level of significance (0.005). In addition, the results of the study stated that the role of sharia can reduce the effect of fair value on earnings management with a significance level of 10% (0.10). However, the role of sharia cannot actually reduce the influence of the board of commissioners on earnings management with a probability level greater than 0.005. Recommendations for further research are expected to be able to trace real earnings management because in this study only using accrual earnings management, then it is expected that the next researcher broadens the sample used and adds other variables that are considered to influence earnings management.